1980
DOI: 10.1083/jcb.85.3.712
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and relaxation of sea urchin sperm flagella by vanadate.

Abstract: Direct measurements of the stiffness (elastic bending resistance) of demembranated sea urchin sperm flagella were made in the presence of MgATP 2-and vanadate. Under these conditions, the flagellum is in a relaxed state, with a stiffness of -0 .9 x 10-2 ' N m l, which is -5% of the stiffness obtained in the rigor state in the absence of MgATP2-. MgADP -'does not substitute for MgATP 2 " in producing the relaxed state . A progressive inhibition of movement is observed after addition of MgATP 2-to flagella prein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
87
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 46 publications
10
87
0
Order By: Relevance
“…Electron microscopy [Goodenough and Heuser, 1982;Burgess et al, 1991;Burgess, 1995] indicates that the ''stalks'' of the dynein motor heads are attached to substrate sites under most conditions. The OFF mode may be similar to the weakly attached state obtained in the presence of ATP and vanadate, which has a very low shear resistance [Okuno, 1980] and supports longitudinal diffusion of microtubules entrapped by dyneins attached to a surface [Vale et al, 1989]. In this view, the ON mode would incorporate a more strongly attached, force producing state that approaches the ''rigor'' state observed in the absence of ATP.…”
Section: Indications For Two Persistent Modes Of Dynein Operationmentioning
confidence: 64%
“…Electron microscopy [Goodenough and Heuser, 1982;Burgess et al, 1991;Burgess, 1995] indicates that the ''stalks'' of the dynein motor heads are attached to substrate sites under most conditions. The OFF mode may be similar to the weakly attached state obtained in the presence of ATP and vanadate, which has a very low shear resistance [Okuno, 1980] and supports longitudinal diffusion of microtubules entrapped by dyneins attached to a surface [Vale et al, 1989]. In this view, the ON mode would incorporate a more strongly attached, force producing state that approaches the ''rigor'' state observed in the absence of ATP.…”
Section: Indications For Two Persistent Modes Of Dynein Operationmentioning
confidence: 64%
“…This and other reports that AMP-PNP also caused the dissociation of dynein arms from isolated outer-doublet microtubules (26), and that relaxation was not blocked (24) (12, 16), were reasonably accommodated by a model that interpreted flagellar relaxation as corresponding to the first step of the mechanochemical cross-bridge cycle of dynein (24). This mechanochemical interpretation of relaxation appears to have remained prevalent despite recent reports by several groups that AMP-PNP does not effect flagellar relaxation (19,20,22,25) .The relationship of ATP binding to flagellar relaxation is important to investigations of dynein mechanochemistry (18,19,24) as well as to an understanding of the role(s) in motility of putative elastic components in the axoneme, since a simple dynein cross-bridge release mechanism implies that flagellar straightening is driven by forces stored in elastic components, such as the nexin links or radial spokes.We have reinvestigated the roles of ATP binding and hydrolysis in the relaxation of rigor-wave sea urchin sperm flagella by using a novel relaxation assay that has permitted the quantitation of the rate as well as the extent of flagellar straightening. Evidence is presented indicating that flagellar relaxation depends on ATP hydrolysis.…”
mentioning
confidence: 96%
“…It was found that (a) the rate of flagellar relaxation induced by 4 x 10 -6 M ATP was inhibited 80% by vanadate concentrations of 3 x 10 -5 M and above; (b) of 16 hydrolyzable and nonhydrolyzable nucleotide di-, tri-, and tetraphosphates tested, only three, each of which was hydrolyzed by the flagellar axonemal ATPase activity (ATP, dATP, and E-ATP), were also capable of effecting relaxation ; (c) several hundred ATP molecules were estimated to be hydrolyzed by each dynein arm in the course of flagellar relaxation ; and (d) the ratio of the rate of relaxation to the rate of ATP hydrolysis, which defines the efficiency of ATP utilization, increased 30-fold as the ATP concentration was raised from 2 x 10 -6 to 9 x 10 -6 M. It is concluded that (a) flagellar relaxation depends on ATP hydrolysis ; (b) because it depends on ATP hydrolysis, flagellar relaxation is an inappropriate model system for investigating the role of ATP binding in the mechanochemical cycle of dynein ; and (c) the efficiency of mechanochemical coupling in flagellar motility is an ATP-dependent phenomenon . A general model of relaxation is proposed based on active microtubule sliding.The relaxation (straightening) of rigor-wave sea urchin sperm flagella is currently favored as a model system for investigating the mechanochemical cycle of flagellar motility (18,19,23,24). This is due to the view that relaxation results from the release of dynein cross-bridges in the flagellar axoneme in response to ATP binding .…”
mentioning
confidence: 99%
See 2 more Smart Citations